2014
DOI: 10.1007/s10393-014-0942-y
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Bushmeat: Animal Contact, Injury, and Zoonotic Disease Risk in Western Uganda

Abstract: Zoonotic pathogens cause an estimated 70% of emerging and re-emerging infectious diseases in humans. In sub-Saharan Africa, bushmeat hunting and butchering is considered the primary risk factor for human-wildlife contact and zoonotic disease transmission, particularly for the transmission of simian retroviruses. However, hunting is only one of many activities in sub-Saharan Africa that bring people and wildlife into contact. Here, we examine human-animal interaction in western Uganda, identifying patterns of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
51
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 35 publications
3
51
1
Order By: Relevance
“…1). Similar to previous findings from the Taï region, Uganda, and Cameroon (11,13,18), contact of women decreased along a gradient of bushmeat freshness (e.g., most women ate, but nearly never hunted, NHP), while men primarily dismembered and hunted NHP. Although this indicates that men are in contact with NHP body fluids more often than women, such contact turned out to be age dependent: for dismembering, cooking, and eating monkeys, contact rates decreased with age in men and increased with age in women.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…1). Similar to previous findings from the Taï region, Uganda, and Cameroon (11,13,18), contact of women decreased along a gradient of bushmeat freshness (e.g., most women ate, but nearly never hunted, NHP), while men primarily dismembered and hunted NHP. Although this indicates that men are in contact with NHP body fluids more often than women, such contact turned out to be age dependent: for dismembering, cooking, and eating monkeys, contact rates decreased with age in men and increased with age in women.…”
Section: Discussionsupporting
confidence: 85%
“…The risk of transmission of retroviruses from NHP is suggested to be greatest during activities involving direct blood contact (8,(10)(11)(12)(13). Hence, if STLVs are prevalent among local NHP, differences in the extent and type of contact with NHP among human populations may contribute to differences in local HTLV-1 prevalence and diversity.…”
mentioning
confidence: 99%
“…Subsequent research has found that risk of human and primate contact is highest for people living in the fragment matrix compared to those who live alongside Kibale National Park itself, despite the fact that KNP is unsurpassed for its primate density and diversity (Paige et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…HIV, malaria, respiratory illness) (Kabarole District Health Statistics Office, 2014). Approximately 20% of the resident population report risky contact with animals (Paige et al, 2014), making the population susceptible to novel zoonotic pathogens.…”
Section: Case Study: the Kibale Hotspotmentioning
confidence: 99%
“…Crop-raiding by wildlife extends shared spaces from the fragment into fields, and hunting by dogs brings wildlife carcasses into the household compound (Goldberg, Paige, & Chapman, 2012). Because of their small areas, proximity to human settlements, and permeable borders, forest fragment systems enable intense and frequent interaction and contact between people and wildlife (Paige et al, 2014). …”
Section: Case Study: the Kibale Hotspotmentioning
confidence: 99%